ANTIBACTERIAL ACTIVITY OF RICINNUS COMMUNIS: IN VITRO STUDY - Al-kuraishy, Hayder; Al-weendy, Salah; Al-buhadilly, Ali; Al-bajajy, Iman; Al-gareeb, Ali; Al-hafied, Ammar (Iraqi Journal of Science, 2024)
Ricinnus communis herb produces significant antimicrobial activity particularly against Gram negative bacteria, in comparison with standard antibiotics. Four bacterial genera were selected two Gram negative (Escherichia coli, and Pseudomonas aeruginosa); and two Gram positive (Staphylococcus aureus, Enterococcus fecalis). These bacterial isolates were incubated and subsequently adding Ricinus communis extracts which were prepared as alcoholic and aqueous solutions .The MIC (Minimal Inhibitory Concentration)was determined for ten isolates of each bacteria . Results showed that the MIC of aqueous extracts ranged between 8-32mg/ml for all selected bacteria while the MIC of the alcoholic extract ranged between 8-16mg/ml. Moreover; the lowest MIC of alcoholic extract was 8mg/ml while the lowest MIC for aqueous extract was 16mg/ml. In conclusion, the alcoholic and aqueous extract generates specific MIC, but the alcoholic extracts produce more particular effects by lower MIC (8 mg/ml). Thus; a topical application of these extracts are useful as alternative antimicrobial remedy regarding the sensitive bacteria.